2013
DOI: 10.1186/1472-6882-13-249
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytocidal effects of the essential oil from Croton cajucara (red sacaca) and its major constituent 7- hydroxycalamenene against Leishmania chagasi

Abstract: BackgroundVisceral leishmaniasis is the most serious form of leishmaniasis and can be lethal if left untreated. Currently available treatments for these parasitic diseases are frequently associated to severe side effects. The leaves of Croton cajucara are used as an infusion in popular medicine to combat several diseases. Previous studies have demonstrated that the linalool-rich essential oil from C. cajucara (white sacaca) is extremely efficient against the tegumentary specie Leishmania amazonensis. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 29 publications
0
34
0
2
Order By: Relevance
“…In addition, an intense exocytic process of cytoplasmic content into the flagellar pocket was noted. Mitochondrion seems to be a common target for several natural products, crude extracts, or isolated compounds, as has been reported by several researchers [10, 2224]. The mode of action of most natural products that cause mitochondrial damage and parasite death has been attributed mainly to sterol biosynthesis inhibition and mitochondrial membrane potential dysfunction [2527].…”
Section: Resultsmentioning
confidence: 96%
“…In addition, an intense exocytic process of cytoplasmic content into the flagellar pocket was noted. Mitochondrion seems to be a common target for several natural products, crude extracts, or isolated compounds, as has been reported by several researchers [10, 2224]. The mode of action of most natural products that cause mitochondrial damage and parasite death has been attributed mainly to sterol biosynthesis inhibition and mitochondrial membrane potential dysfunction [2527].…”
Section: Resultsmentioning
confidence: 96%
“…Natural products isolated from H. inuloides and semisynthetic derivatives that were assayed for activity against Giardia intestinalis. Although several compounds isolated from H. inuloides have antiinflammatory activity (Delgado et al 2001) and it has been found that the 7-hydroxycalamenene shows activity against Leishmania chagasi promastigotes with a minimum inhibitory concentration of 15·6 μg mL − 1 (Rodrigues et al 2013), this is the first report that 1 and 14 can act as antigiardial agents. The failure rates reflect the need for more alternatives for treating giardiasis.…”
Section: Discussionmentioning
confidence: 82%
“…Our in vitro results in amastigotes also revealed better activity than other EOs obtained from Cuban plants, including Artemisia absinthium L. (Asteraceae), IC 50 = 13.4 μg/mL (Monzote et al ., ), and Bixa orellana L. (Bixaceae) IC 50 = 8.5 μg/mL (Monzote et al ., 2014 b). In addition, a lower IC 50 value was also obtained than some EOs reported in the literature: Croton cajucara Benth (Euphorbiaceae), IC 50 = 66.7 μg/mL (Rodrigues et al ., ); Lippia sidoides Cham (Verbenaceae), IC 50 = 44 μg/mL (de Medeiros et al ., ); Vanillosmopsis arborea Baker (Asteraceae), IC 50 = 12.6 μg/mL (Colares et al ., ); Aristolochia cymbifera Mart (Aristolochiaceae); Lippia alba (Mill.) N.E.Br.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that about 25% of medicines are derived directly or indirectly from herbal products (Kunle et al, 2012). Within the group of natural products, essential oils (EOs) have been of interest because of their broad spectrum of reported biological properties (Kulevanova et al, 2000;Rhayour et al, 2003), including leishmanicidal activity (de Medeiros et al, 2011;Rodrigues et al, 2013;Colares et al, 2013;Monzote et al, 2014a,b). In addition, their hydrophobic nature makes these oils more permeable to cells (Burt, 2004), which is a very important feature for developing agents against intracellular pathogens.…”
Section: Introductionmentioning
confidence: 99%